Answer:
![(2)/(3)\text{ feet}](https://img.qammunity.org/2020/formulas/mathematics/high-school/tvdgiw01v5zj6p5emwavcbvc5nyrny4sog.png)
Explanation:
Let the equation that models the height of the tree after x years,
y = mx + c
Where, m is constant amount of increasing and c is any constant,
Given,
When x = 0, y = 4,
⇒ 4 = m(0) + c ⇒ c = 4,
Now, the height of plant after 4th year = m(4) + c = 4m + c
Also, the height of plant after 6th year = m(6) + c = 6m + c
According to the question,
6m + c is
more than 4m + c,
![6m+c=4m+c + (1)/(5)(4m+c)](https://img.qammunity.org/2020/formulas/mathematics/high-school/pxtietvqhbcswwe3nppouzhfzcz2n177ve.png)
![6m+c = (6)/(5)(4m+c)](https://img.qammunity.org/2020/formulas/mathematics/high-school/gqu8m4k6f3kri13klh462r4qdwss4yil6n.png)
![30m+5c=24m+6c](https://img.qammunity.org/2020/formulas/mathematics/high-school/kgwywc4x8aovoc1re53ldpsr2lbz5cy4hs.png)
![6m=c](https://img.qammunity.org/2020/formulas/mathematics/high-school/bzqlobofiwwgxl4hgpp08majefi57woqil.png)
By substituting the value of c
6m = 4
⇒
![m=(4)/(6)=(2)/(3)](https://img.qammunity.org/2020/formulas/mathematics/high-school/6r8ti11ofyh4g01ovj725pdsv2bw89325s.png)
Hence, 2/3 feet of height is increased each year.